Food consumption and disease risk : consumer-pathogen interactions - Potter, Morris E. (CRC Press ; Woodhead, 2006)
Annotation Factors which influence interactions between foodborne pathogenic agents and consumers, therefore affecting the risk of consumers catching foodborne diseases are essential knowledge for microbiologists, R & D and QA staff in the food industry. This collection reviews important issues in the relationship between consumers and foodborne bacteria, viruses and parasites. The first part presents a broad picture of aspects that increase or decrease exposure to foodborne pathogens, such as globalization of the food supply and trends in food processing. The second and third parts focus on host factors that influence foodborne disease (e.g. age, genetics and underlying illness) and characteristics of pathogenic agents that influence interaction with human hosts. CONTENTS Part 1 Factors that influence interactions between foodborne pathogens and consumers: Social and anthropologic factors; Globalization of the food supply and economic factors; Trends in agricultural management and land use; Influence of food processing practices and technologies; Exposure assessment for foodborne pathogens. Part 2 Host factors that influence foodborne disease: Nonspecific host defences against foodborne pathogens; Specific immune mechanisms of defence; Effects of age on resistance to foodborne infections; Enhanced susceptibility to foodborne infections due to illness and pregnancy; Genetics of susceptibility to foodborne diseases. Part 3 Agent factors of pathogenicity and virulence: Microbial adaptation to host defenses and environmental adversity; Mechanisms of microbial colonization; Environmental virology and foodborne disease; Pathogenic mechanisms of foodborne parasitic disease.
Keywords: Foodborne diseases -- Risk factors.; Foodborne diseases -- Prevention.; Pathogenic microorganisms.; Public health -- International cooperation.; Food industry and trade -- Safety measures.; Food poisoning.; International cooperation.; Food industry and trade.; Food -- Microbiology.; Public health.; elektronické knihy; electronic books